Voting on thresholds for public goods: experimental evidence - Julian Rauchdobler; Rupert Sausgruber; Jean-Robert Tyran (Center for Economic Studies and ifo Institute (CESifo), 2009)
Introducing a threshold in the sense of a minimal project size transforms a public goods game with an inefficient equilibrium into a coordination game with a set of Pareto-superior equilibria. Thresholds may therefore improve efficiency in the voluntary provision of public goods. In our one-shot experiment, we find that coordination often fails and exogenously imposed thresholds are ineffective at best and often counter-productive. This holds under a range of threshold levels and refund rates. We test if thresholds perform better if they are endogenously chosen, i.e. if a threshold is approved in a referendum, because voting may facilitate coordination due to signaling and commitment effects. We find that voting does have signaling and commitment effects but they are not strong enough to significantly improve the efficiency of thresholds.
Keywords: H41; D72; C92; 330; provision of public goods; threshold; voting; experiments